Edukasi Bahaya Penyalahgunaan Obat (NAPZA) pada Generasi Muda di SMPN 1 Cimalaka Melalui Program SEHAT (Sosialisasi Efektif Hindari Obat Terlarang): Pengabdian - Moch Alif Haqi; Hanaa Azkia; Naila Joya; Fathia Hanifa Syahida; Ihsan Firmansyah; Neng Dina Agustina; Mochammad Reihan Rabbani; Muhammad Dwiky Nugraha; Ayu Safitri; Riva Rivanti; Muhtadin (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The SEHAT (Effective Socialization to Avoid Illegal Drugs) program is carried out at SMPN 1 Cimalaka with the aim of increasing students' knowledge and awareness of the dangers of narcotics, psychotropics, and other addictive substances (NARCO). This study uses an extension method with a community education approach, involving 60 students as respondents. Activities include a pre-test to measure initial understanding, socialization of material regarding drug classification, packaging symbols, the impact of abuse, and legal aspects, and ended with a post-test to evaluate effectiveness. The results showed a significant increase in knowledge, with the average post-test score increasing by 44.9% compared to the pre-test. In addition, students show enthusiasm and active participation during socialization. These findings show that the SEHAT program is effective in increasing students' understanding and awareness of the dangers of drug abuse from an early age.